Development of Rocket Telemetry in Chamber Gas Pressure Monitoring with the MPXV7002DP Gas Pressure Sensor - Anggara Trisna Nugraha; Dadang Priyambodo (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
Telemetry is a process used to measure or record a physical quantity at a location far from the center of processing the measurement results. Telemetry systems on unmanned aerial vehicles can provide information such as position, altitude, direction, and status of the vehicle itself in real time when the air vehicle is operated. A rocket is a flying vehicle that moves by getting a boost through the combustion reaction that occurs in the rocket. Implementation of the strain gauge sensor through the MPXV7002DP gas pressure sensor, the amount of gas pressure is obtained at the time of combustion of the rocket and sent via wi-fi telemetry Pixhawk 447 MHz, the data on a laptop can be shown the gas pressure generated in the rocket chamber through the display of the Borland Delphi program with a distance of 150 m.